Factors Associated with Depression among Type 2 Diabetes Mellitus Patients at a Tertiary Hospital during the COVID-19 Pandemic - Mokoagow, Muhammad Ikhsan; Pitawati, Dian; Arisandy, Ditya Nona; Magfira, Nadya; Palupi, Pratiwi Indah; Nasarudin, Jerry; Epriliawati, Marina; Kshanti, Ida Ayu (UI Scholars Hub, 2022)
Diabetes mellitus is a metabolic disorder characterized by chronic hyperglycemia that can cause various complications, economic burdens, and psychosocial issues that eventually lead to depression. This study aimed to describe the prevalence of depression among type 2 diabetes mellitus patients in the Internal Medicine Outpatient Clinic of a South Jakarta tertiary hospital during the COVID-19 pandemic. This cross-sectional study was conducted from May to July 2021. The data were collected consecutively from 100 patients aged 18 years or older who came for regular consultation. The instrument used for determining depression is Beck Depression Inventory-II. The prevalence of depression, a correlation between depression and participants' characteristics, and multivariate analysis for risk factors were determined. The results showed that the prevalence of mild to severe depression based on the BDI-II classification was 17%. Screening showed mild to severe depression predominantly in females above 60 years old, with higher levels of education, obesity grade I, individuals with one or more comorbidities, and those who had diabetes for more than ten years. In this study, having one or more comorbidities was associated with an increased risk of depression in people with diabetes.